Efektivitas Metode Pembelajaran Berbasis TBLA dengan Memanfaatkan Prior Knowledge dan Kearifan Lokal dalam Pembelajaran Bahasa Indonesia di SDS Soekarno Hatta - Ratnaningsih, Dewi; Hartono; Aprilia, Rida; Kristina, Marilin (Edukasi Lingua Sastra, 2025)
This study examines the effectiveness of a Task-Based Language Assessment (TBLA) method integrated with students' prior knowledge and the local wisdom of Piil Pesenggiri in Indonesian language learning. The research employed the ADDIE model combined with lesson study, involving fifth-grade elementary students as subjects. Results demonstrated significant improvements in: (1) average learning outcomes (77.25, categorized as "good"), (2) critical thinking skills (25% increase), and (3) discussion participation (30% increase). TBLA transcript analysis revealed that incorporating nemui nyimah (hospitality) and sakai sambayan (mutual cooperation) values created contextual and inclusive learning. The STAD model effectively enhanced student collaboration, with 85% of groups showing productive interactions. These findings confirm that culturally-grounded TBLA approaches not only improve language competence but also strengthen cultural identity. The study recommends using authentic tasks based on local wisdom, transcript analysis for teacher reflection, and adaptive performance-based assessment. Practical implications include designing Indonesian language instruction that aligns with students' socio-cultural contexts.